Prospective evaluation of XRCC‐1 Arg194Trp polymorphism as bio‐predictor for clinical outcome in locally advanced laryngeal cancer undergoing cisplatin‐based chemoradiation. Issue 5 (30th January 2020) - Raturi, Vijay; Hojo, Hidehiro; Bhatt, M. L. B.; Suhel, Mohammad; Wu, Chen‐Ta; Bei, Yanping; Nakamura, Masaki; Okumura, Masayuki; Zhang, Haiqin; Parmar, Devendra; Badajena, Avinash; Singh, Rahul; et al.
Abstract: Background: To determine X‐ray repair cross‐complementing 1 gene (XRCC‐1) Arg194Trp polymorphism as bio‐predictor for clinical outcome in advanced laryngeal squamous cell carcinoma undergoing cisplatin‐based chemoradiation (CRT). Methods: A total of 150 patients were enrolled in this prospective study. XRCC‐1 Arg194Trp genotyping categorized patients as wild (C/C) and polymorphic (C/T or T/T). The primary endpoint was to assess acute radiation‐induced toxicity (ARIT). Results: A significant correlation of skin ( P‐ .04) and oral mucosal ARIT ( P ‐ .01) was noticed in the XRCC‐1 polymorphic variant. A higher treatment response was noted in the polymorphic variant, and it shows a trend toward significance ( P‐ .08). With 33 months of median follow‐up, 2‐year progression‐free survival (PFS) and overall survival (OS) of wild vs polymorphic variant were 34.6% vs 46.9% ( P‐ .066) and 50.6% vs 62.2% ( P ‐ .12). Conclusion: XRCC‐1 polymorphic variants have significantly higher oral mucositis and skin ARIT and may have improved trend for treatment response and PFS.